2012
DOI: 10.1242/jeb.071522
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic cost of walking on gradients with a waddling gait

Abstract: SUMMARYUsing open-flow respirometry and video footage (25framess -1 ), the energy expenditure and hindlimb kinematics of barnacle geese, Branta leucopsis, were measured whilst they were exercising on a treadmill at gradients of +7 and -7deg, and on a level surface. In agreement with previous studies, ascending a gradient incurred metabolic costs higher than those experienced on level ground at comparable speeds. The geese, however, are the first species to show an increased duty factor when ascending a grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 60 publications
2
9
2
Order By: Relevance
“…This method, however, relies on a difference between the regression slopes. In the present study, in common with findings in mice, crabs, quail and more recently geese, the MCoT did not differ upon incline locomotion in either season (Nudds and Codd, 2012;Taylor et al, 1972;Tullis and Andrus, 2011;Warncke et al, 1988). Applying the traditional approach to such data would therefore reveal no additional cost of lifting despite absolute energy expenditure values clearly being higher during incline locomotion.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This method, however, relies on a difference between the regression slopes. In the present study, in common with findings in mice, crabs, quail and more recently geese, the MCoT did not differ upon incline locomotion in either season (Nudds and Codd, 2012;Taylor et al, 1972;Tullis and Andrus, 2011;Warncke et al, 1988). Applying the traditional approach to such data would therefore reveal no additional cost of lifting despite absolute energy expenditure values clearly being higher during incline locomotion.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings have been demonstrated in humans, although the curvilinear nature of metabolic cost during walking makes comparison with avian data problematic (Margaria et al, 1963). In the only avian studies to use solely walking gaits, quail on inclines of 4, 8 and 12deg shared a common slope and geese on inclines of 7deg showed no difference in MCoT compared with that on level ground (Nudds and Codd, 2012;Warncke et al, 1988). The results of both studies are in agreement with our findings, highlighting the importance of gait when measuring the energetic cost of locomotion.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Studies investigating the effects of incline locomotion on kinematic parameters have found differences in DF ( Dutto et al, 2004 ), stride frequency ( Gillis & Biewener, 2002 ) and t stance (the relative amount of time a foot is on the ground during a stride ( Hoyt, Wickler & Cogger, 2000 )) between level and incline locomotion. Force generation during t stance is a direct measure of the metabolic cost of locomotion, and stride frequency has been directly associated with energetic cost, yet relatively few studies have investigated the metabolic cost of incline locomotion with the associated kinematic changes ( Heglund et al, 1982 ; Lees et al, 2013 ; Nudds & Codd, 2012 ). Because the rate of force production is the parameter of interest, the inverse of contact time (1/ t stance ) is used for analysis and gives a measure of force application ( Kram & Taylor, 1990 ).…”
Section: Introductionmentioning
confidence: 99%